(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Marketing automation is a relatively new area within the online marketing landscape. Marketing automation systems are a type of management information systems (MIS) used in customer relationship management (CRM). These systems have gained popularity with large clients who are looking to develop their online strategy. There are several large vendors of marketing automation software. The aim of the paper is to present the evolution of usage of one of the top software tools in the email marketing area, looking for correlations between database sizes and sending volumes, as well as identifying sending volume patterns depending on the calendar. The focus is on a specific software tool used for marketing automation and its largest EU customers by email marketing database size. The core feature of such a tool is sending emails; therefore, this will be our prime indicator of reach that will be presented in correlation to database size, email open and email click rates. Data interpretation and the research implications will be included in the conclusion and will show an important increase in the use of email marketing and strong correlations amongst used indicators.